Does the experience of anatomical dissections change the mind of students? The opinion of Milanese undergraduate students towards the donation of bodies for didactic purposes - Gibelli, Daniele; Ferrario, Virgilio F.; Dolci, Claudia; Sforza, Chiarella (Italian Journal of Anatomy and Embryology, 2017)
Anatomical dissections have always represented an important cornerstone of medical education, especially in anatomy [1,2]. However, in several universitary context their practice has been abandoned or even not yet introduced. In the University of Milan a limited program of body donation has existed since 2014 (PANDORA, Programma Anatomico di Donazione di Cadaveri a Scopo di Ricerca Antropologica e Biomedica) and therefore only in the last four years medical students have been able to take advantage from this crucial experience. This study aims at exploring the willingness of Italian undergraduate students towards whole body donation in order to ascertain the role of dissection in modifying the opinion: two groups of students belonging to the degree course in medicine and surgery were recruited. The first group included 43 students who were informed concerning the importance of dissection in anatomy through a specific course. The second group included 29 students admitted to a didactic autopsy. Students belonging to the two groups were then requested to specify if they would give their consent to the donation of their bodies, and why. Results showed that students who attended the dissection were more likely to show willingness towards body donation (60.7% versus 39.5%). Among positive opinions towards donation the percentage of persons who found the experience useful increased from 47.1% in the first group to 80% in the second group. On the other hand, among negative opinions, percentages of persons reporting bad feeling towards the dissection increased from 16.7% in the first group to 27.2% in the second group. This study shows that experience of dissection is a crucial step for emotional and professional improvement of medical students and contributes in a more detailed definition of their own opinion concerning body donation.